2018
DOI: 10.1038/s41467-018-05536-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct quality control of glycoengineered erythropoietin variants

Abstract: Recombinant production of glycoprotein therapeutics like erythropoietin (EPO) in mammalian CHO cells rely on the heterogeneous N-glycosylation capacity of the cell. Recently, approaches for engineering the glycosylation capacities of mammalian cells for custom designed glycoforms have been developed. With these opportunities there is an increasing need for fast, sensitive, and global analysis of the glycoproteoform landscape produced to evaluate homogeneity and consistency. Here we use high-resolution native m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 34 publications
2
85
0
Order By: Relevance
“…After overexpression of EPO, glycans were cleaved using PNGase, and then assayed by mass spectrometry. Upon retrieval of these data from the study, we picked 16 glycoprofiles that are used again in their following up study 11 and further processed the data as follows. All measurements were taken from distinct samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After overexpression of EPO, glycans were cleaved using PNGase, and then assayed by mass spectrometry. Upon retrieval of these data from the study, we picked 16 glycoprofiles that are used again in their following up study 11 and further processed the data as follows. All measurements were taken from distinct samples.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrate the functionality and performance of this approach with both protein-conjugated and unconjugated glycomic analysis, using recombinant erythropoietin (EPO) N-glycosylation and human milk oligosaccharides (HMOs). Specifically, we analyzed sixteen MALDI-TOF glycoprofiles of EPO, where each EPO glycoprofile was produced in a different glycoengineered CHO cell line 9,11 . We also analyzed forty-eight HPLC glycoprofiles of HMO from six mothers 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess sortase-mediated conjugation a small nucleophilic peptide (GGGCK(FAM)) was Orbitrap instrument with extend mass range (EMR) as described before (42). Intact Mass software was used for zero-charge deconvolution of the spectra to determine the antibody mass (43).…”
Section: Sortase-mediated Ligationmentioning
confidence: 99%
“…3,[6][7][8][9] Glycan is a major structural moiety that has important effects on the pharmacokinetics and pharmacodynamics of EPO analogues such as darbepoetin alfa and epoetin alpha and beta. [10][11][12][13] The structure of glycan in EPO plays an important role in various biological activities. First, several studies have shown that sialic acid capping of the terminal galactose residue prevents hepatic clearance of EPO.…”
Section: Introductionmentioning
confidence: 99%